The Relationship Between Peer Interaction and Emotional Intelligence of Grade V Students at Elementary School Inpres 1 Birobuli - Dewi Fitriana; Herlina Herlina; Asriani Asriani; Rizal Rizal; Dyah Aini Purbarani (Journal of Educational Sciences, 2026)
The research entitled “The Relationship Between Peer Interaction and Students' Emotional Intelligence at SD Inpres 1 Birobuli” is motivated by the importance of social interaction among elementary school students. In practice, some students still show individualistic tendencies, difficulty empathizing, and limited ability to manage emotions and establish social relationships. This condition encourages the need to examine the role of peer interaction in students’ emotional intelligence. This study aims to determine the relationship between peer interaction and the emotional intelligence of fifth-grade students at SD Inpres 1 Birobuli. The research employed a quantitative approach with a correlational design. The subjects consisted of 23 students selected using a total sampling technique. Data were collected through peer interaction and emotional intelligence questionnaires, supported by documentation. Data analysis used descriptive and inferential statistics with the Pearson Product Moment correlation test. The results showed a positive and significant relationship between peer interaction and students’ emotional intelligence at a significance level of 0.05, with a correlation coefficient (r) of 0.680, indicating a strong relationship. Thus, it can be concluded that better peer interaction contributes to higher emotional intelligence among elementary school students.